Influence of particle shape on pebble transport in a mixed sand and gravel beach during low energy conditions: Implications for nourishment projects. (1st March 2019) - Grottoli, Edoardo; Bertoni, Duccio; Pozzebon, Alessandro; Ciavola, Paolo
Abstract: Beach nourishments using coarse-gravel sediments are becoming a frequent practice to buffer coastal erosion, but usually little attention is spent on fill material characteristics. A better understanding of the influence of sediment characteristics on transport is crucial to establish the best compatibility of fill material with native beach sediments. Pebble transport is here investigated by means of the RFID tracing technique. The main purpose of the experiment was to verify whether the prevalent shapes populating the beach (disks and spheres) show a different transport under low energy conditions. Tracers were injected in a small and straight portion of a mixed sand and gravel beach, deploying couples of marked particles of the same size (one sphere and one disk-shaped pebble on the main geomorphic elements of the beach face), in order to avoid size influence on transport. Tracer recovery was undertaken 6 and 24 h after the injection and wave characteristics were measured during the whole experiment duration by means of a S4 directional wave gauge. After 6 h the marked pebbles underwent significant displacement with a prevalent longshore component, which became evident after 24 h. The swash zone proved to be the most dynamic area of the beach. Spheres covered longer distances and resulted more dynamic than disks, thanks to their capability to roll-over in the swash zone. Lately, many experiments have been carried out with marked pebbles, but this is the first time that an experiment is conceived to prove how shape influences pebble transport. Disks are more subject to burial and due to their higher dynamicity spheres are preferred to disks for nourishment fill material. A fill material comprised of spheres is regularly responding to hydrodynamic forces and can positively speed up the beach recovery after storms especially in highly dynamic systems like pocket beaches, typically subjected to beach rotation processes. The results show an implication for coastal managers having to choose fill sources for replenishments. Highlights: Particle shape has implication for the choice of fill material in gravel nourishments. Spheres can positively speed up the beach recovery after storms. Disks are less dynamic and more subject to imbrication and burial by other sediments. Nourishment schemes should prefer a spherical shape for fill material. Studies on particle shape are needed to better estimate gravel nourishment lifetime.